The impact of digital technology usage on human resource management effectiveness in KPJ Kluang Utama Specialist Hospital - Ab.Rahman, Nursahina Fatima (2018)
By using the resource-based view of the Human Resources Management (HRM), the purpose of this study is to investigate the impact of digital technology usage on HRM effectiveness. The objective of this study is to investigate the employee’s motivation, easiness in using technology, efficiency and system delivery and services of technology usage towards HRM effectiveness. There are four hypotheses were developed to identify whether there is positive relationship between employee’s motivation, easiness in using technology, efficiency and system delivery and services towards HRM effectiveness. The questionnaire was distributed to 150 respondents. Descriptive, correlation and regression analysis were used to analyse data. The result from Pearson Correlation Analysis showed that there is a positive, significant and moderate association between easiness in using technology, efficiency and system delivery with HRM effectiveness. Moreover, there is positive, significant and weak association between employee’s motivations with HRM effectiveness. Furthermore, based on R2, it is means that 31.8% of the variance on the HRM effectiveness can be explained by four independent variables while other 68.2% cannot be explained. According to the result of multiple regression analysis, there are two independent variable which are easiness in using technology and efficiency have a significant relationship toward HRM effectiveness. The other two independent variables which are employee’s motivations and system delivery and services have not significant relationship toward HRM effectiveness in KPJ Kluang Utama Specialist Hospital. Lastly, the organization should know the factors that can contribute to the technology usage on HRM in the organization.